2016
DOI: 10.1007/s40888-016-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

A new look at oil price pass-through into inflation: evidence from disaggregated European data

Abstract: This paper analyzes oil price pass-through into inflation at disaggregate level for the euro area and its four main economies (France, Germany, Italy and Spain). The pattern of responses to oil price changes is quantitatively diverse across economies and across items of disaggregate inflation. Moreover, we suggest an alternative method to the direct calculation of aggregate effects on inflation given that indirect and second-round effects may offset the positive effects found in energy inflation and dissipate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Similar results were found in other economies also. For instance, (Castro, Jiménez-Rodríguez, Poncela, & Senra, 2017) found that oil price shocks worsen inflation in European economies. Choi et al (2018) also discovered a similar result with an asymmetric effect in different developed and developing economies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in other economies also. For instance, (Castro, Jiménez-Rodríguez, Poncela, & Senra, 2017) found that oil price shocks worsen inflation in European economies. Choi et al (2018) also discovered a similar result with an asymmetric effect in different developed and developing economies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, among the oil exporting nations too the diversity on impact of oil price pass through can be seen. Castro et al (2017) in a study of four major European economies Germany, France, Spain and Italy found diverse pattern across disaggregate economy. Karimili et al (2016) has found oil price shock significantly affecting domestic inflation in Russia, Azerbaijan and Kazakasthan.…”
Section: Review Of Literaturementioning
confidence: 98%
“…Among them, significant impacts from oil price changes are found prices for industries of food (Ibrahim, 2015), agricultural (Zhang, Lohr, Escalante, & Wetzstein, 2010) and transportation (Hansman, 2014). Castro, Jiménez-Rodríguez, Poncela, and Senra (2017) focused the investigation in Euro area (France, Germany, Italy and Spain). The results reveal that oil price changes have a large and direct effect on energy inflation but the impact to total inflation is weak.…”
Section: Literature Reviewmentioning
confidence: 99%